Utilization of Learning Media in Conditioning Classes in Fiqh Learning at Madrasah Tsanawiyah - Rahmadani, Putri Suci; Nurmawati, Nurmawati (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This study aims to analyze the use of media in conditioning classes in Fiqh learning at Madrasah Tsanawiyah in class VIII-1. The media used is a wall magazine (mading) which functions as an aid that can create a conducive, interesting, and interactive learning atmosphere. The method in this study uses a qualitative approach with 3 data collection techniques, namely observation, interviews with three informants and documentation studies. The data analysis technique used is to analyze the results of observations, interviews, and documentation, then reduce the data so that the results obtained are in accordance with the indicators and focus of the study, and then draw conclusions from the final results. The results of this study indicate that wall magazine media (mading) can increase students' interest in learning, strengthen their understanding of Fiqh concepts, and encourage active student participation in the learning process. In addition, this wall magazine media (mading) provides a creative space for students to convey ideas and opinions related to Fiqh learning and can make the classroom atmosphere more conducive when explaining the subject matter.